Матеріали для виготовлення мікросхем на основі 3D технологій - Білокінь, В. К. (ХНУРЕ, 2025)
The study explores the use of 3D printing as one of the promising methods for manufacturing microelectronic components, particularly from powdered metals. The research examines the physicochemical properties of powdered metals, their technological suitability for additive manufacturing, and the main challenges associated with production costs and the need for material standardization. Special attention is given to the application of 3D printing in the production of microchip enclosures using polymer materials. The characteristics of key thermoplastic polymers, such as PLA, PETG, and ABS, are analyzed, along with their advantages and limitations in the context of microelectronics.
Keywords: виготовлення мікросхем; 3D printing